Avaliação não-invasiva da fibrose hepática - Tramontin, Giacomo (2021)
Introduction: Early assessment of the degree of liver fibrosis is essential to estimate prognosis, plan treatment strategies, and intervene to significantly impact disease progression. The aim of this study was to determine the prevalence of significant and advanced liver fibrosis evaluated by elastography magnetic resonance. Materials and methods: This was a retrospective cross-sectional study. Adult patients of both genders who underwent elastography by magnetic resonance from January to July 2018 were included. Demographic and clinical data were collected from the patients' electronic medical records. Abdominal magnetic resonance images were interpreted by two specialist radiologists with at least five years of experience in the field of abdominal radiology. Results: 119 patients were enrolled in the study. There was a predominance of males (58.8%), and the mean age was 52.5 ± 12.8 years. The mean body mass index was 29.0 ± 5.6 kg/m2 and 77.0% had overweight. The mean liver stiffness value was 2.9 kPa (95% CI 2.7 – 3.1). Fifty-five (46.2%) patients presented fatty liver, and 32 (26.9%) were classified as mild, 17 (14.3%), as moderate, and six (5.0%), as severe degree. Significant and advanced fibrosis was 9.2% and 20.2%, respectively. Readers R1 and R2 had an excellent agreement for measured liver stiffness values (k=0.929; p<0.001). In multivariate analysis, diabetes mellitus was associated with liver stiffness only in the unadjusted analysis. In the other models, there was no association between the analyzed variables and liver stiffness Conclusions: Magnetic resonance elastography detected a high prevalence of significant and advanced liver fibrosis in a population in southern Brazil. Furthermore, diabetes mellitus was shown to be an independent factor associated with increased liver stiffness.